Modeling, Control and Optimisation of Hybrid Systems in a Manufacturing Setting - Mashaba, Kobamelo (Curtin University, 2020)
This study comprises a body of work that investigates the performance of hybrid manufacturing systems. And we have provided a valuable insight into the development of the optimisation techniques for hybrid manufacturing system. With the primary objective of developing prac-tical mathematical algorithms that balance trade-o? cost between product quality and completion time. For sta-bility criterion, a sliding mode control was deployed.